Synchronous gastric and colonic cancer – A case report - Trifunović, Bratislav; Nešković, Branimir; Bezmarević, Mihailo; Kršić, Jovan; Veljović, Milić; Zeljković, Dejan (Vojnosanitetski pregled, 2015)
Introduction. Synchronous gastric and colorectal cancer is present in 4% of cases, commonly as additional finding. This is the case of invasive, synchronous gastric and sigmoid colon cancer. Case report. A 63-years-old male patient admitted to our institution complaining on pains in epigastrium, vomiting, rapid weight loss and occasional constipation. Using the method of esophagogastroduodenoscopy (EGD) the presence of ulcero-infiltrative tumor of gastric fundus was verified, and colonoscopy revealed stenosing tumor of sigmoid colon. Undergoing a multislice computed tomography (MSCT) of the thorax and the abdomen the changes on the patient’s right lung appeared, while video-assisted thoracoscopy (VATS) and biopsy of the right lung excluded malignant dissemination. A total gastrectomy with omentectomy, splenectomy, D2 lymphadenectomy and typical left hemicolectomy were also performed. Histopathological examination verified invasive, diffuse gastric adenocarcinoma and invasive, tubular colon adenocarcinoma. The patient underwent systemic postoperative chemotherapy. Two years after the surgical procedure, the patient is alive, with no signs of recidivism. Conclusion. In patients with symptomatology which does not correspond to primary malignancy, just like in the presented case, additional diagnostics is required. Combined resection is adequate surgical procedure for synchronous gastric and colonic cancer.
Keywords: neoplasms; multiple primary; stomach neoplasms; colonic neoplasms; diagnostic techniques and procedures; histology; digestive system surgical procedures